Decentralization and Corruption : New Cross-country Evidence - Ivanyna, Maksym; Shah, Anwar (2012)
We attempt to improve the understanding and measurement of decentralization and its relationship with corruption in a worldwide context. This is done by presenting the conceptual underpinnings of such a relationship as well as using more defensible measures of both decentralization in its various dimensions as well as corruption for a sample of 158 countries. It is the first paper that treats various tiers of local governments (below the intermediate order of government) as the unit of comparative analysis. By pursuing rigorous econometric analysis we demonstrate that decentralization, when properly measured to mean moving government closer to people by empowering local governments, is shown to have a significant negative effect on the incidence of corruption regardless of the choice of the estimation procedures or the measures of corruption used. In terms of various dimensions of decentralized local governance, political decentralization matters even when we control for fiscal decentralization. Further voice (political accountability) is empirically shown to be more important in combating corruption than exit options made available though competition among jurisdictions.